Bentuk Tanggung Jawab Perusahaan Investasi atas Kerugian Nasabah Akibat Pembubaran dan Likuidasi Produk Reksa Dana - Merthafanny Soetektjo; Sylvia Janisriwati; Elly Hernawati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
PT MPAM as an Investment Manager who trades one of the instruments in the form of mutual funds in the form of KIK and shares. In this case PT MPAM did not carry out its obligations in terms of making phase II refund payments to approximately 6,000 customers as a result of the dissolution of 6 (six) mutual fund products. For this reason, PT MPAM did not fulfil the statutory provisions, namely Article 27 of Law No. 8 of 1955 in conjunction with Article 47 letter b, Article 61 letter b and Article 63 letter g of OJK Regulation Number 23/POJK.04/2016, which resulted in a default . PT MPAM does not comply with the statutory provisions as mentioned above, which does not carry out its obligations as an Investment Manager to make payment of refunds for phase II dissolution of 6 (six) mutual fund products which causes Customers to suffer losses of approximately 6 (six) Trillion. The second stage payment was promised to be made in an in-kind scheme on 18 May 2020 but for 2 years PT MPAM did not carry out its obligations or achievements, so in this case PT MPAM must be responsible for the losses of customers as regulated in Article 111 of Law No. 8 1955 in conjunction with Article 29 of OJK Regulation No. 1/POJK.07/2013. In addition, PT MPAM is also liable on the basis of default in accordance with Article 1243 of the Civil Code, where all elements of the default have been fulfilled. Keywords: Mutual Funds; Default; Liability.